Mesonephric Adenocarcinoma of the Vagina Harboring TP53 Mutation - Hyunjee Lee; Hyunjin Kim; Hyun-Soo Kim (Diagnostics, 2022)
Mesonephric adenocarcinoma (MA) of the female genital tract is a rare but distinct entity, exhibiting unique morphological, immunophenotypical, and molecular characteristics. Vaginal MA is hypothesized to arise from the mesonephric remnants located in the lateral vaginal wall. A 52-year-old woman presented with vaginal bleeding. Physical examination revealed a protruding mass in the left vaginal wall. Pelvic magnetic resonance imaging revealed a 2.5-cm mass arising from the left upper vagina and extending posterolaterally to the extravaginal tissue. The punch biopsy was diagnosed as poorly differentiated adenocarcinoma. She received radical surgical resection. Histologically, the tumor displayed various architectural patterns, including compactly aggregated small tubules, solid cellular sheets, endometrioid-like glands and ducts, intraluminal micropapillae, cribriform structure, and small angulated glands accompanied by prominent desmoplastic stroma. The tubules and ducts possessed hyaline-like, densely eosinophilic intraluminal secretions. The tumor extended to the subvaginal soft tissue and had substantial perineural invasion. Immunostaining revealed positivity for the mesonephric markers, including GATA3, TTF1, and PAX2, while showing very focal and weak positivity for estrogen receptor and negativity for progesterone receptor. Additionally, we observed a complete absence of p53 immunoreactivity. Targeted sequencing analysis revealed that the tumor harbored both activating KRAS p.G12D mutation and truncating TP53 p.E286* mutation. A thorough review of the previous literature revealed that 4.5% (3/67) of vaginal/cervical MAs and 0.9% (1/112) of uterine/ovarian mesonephric-like adenocarcinomas harbor TP53 mutations, indicating that this is very uncommon in malignant mesonephric lesions. In summary, we presented a rare case of vaginal MA uniquely harboring pathogenic TP53 mutation, resulting in p53 aberration.